(untitled) (Bangladesh Journal of Child Health, 2025)
Background: Pancreatitis-related morbidity and mortality are high. Early diagnosis and prompt treatment are essential to reduce mortality and morbidity. Etiological, clinical, biochemical and imaging studies are crucial for early diagnosis and treatment. Objectives: To observe the etiological, clinical, biochemical, and imaging profiles of acute, acute recurrent and chronic pancreatitis in children. Methods: This cross-sectional descriptive study was conducted at the Pediatric Gastroenterology and Nutrition Department of BSMMU. A total of 72 consecutive patients aged 3 to 18 years who fulfilled the inclusion criteria of pancreatitis were enrolled in this study from June 2017 to July 2020. The diagnosis of pancreatitis was based on INSPPIRE criteria for the diagnosis of pancreatitis. The data were analyzed with the SPSS for Windows version 23.0. The variables studied were described as frequencies and percentages or as means ±SD; the p-value reached from the ANOVA test, and p< 0.05 was considered statistically significant. Results: Among the cases, 52.8% were male. The frequency of pancreatitis was higher in the 5–10-year age group. The mean age was 10.27±3.71years. Among all cases, 41.7% had acute pancreatitis, 31.9% chronic pancreatitis, and 26.4% had acute recurrent pancreatitis. The etiology of pancreatitis was idiopathic (54.1%) in most cases. Obstructive and genetic causes were found to be the causes in 19.4% cases each. Characteristic abdominal pain was the presenting feature of all forms of pancreatitis. No significant difference was observed in the laboratory parameters among all three types of pancreatitis. Plain X-ray abdomen showed normal radiological findings in most cases. On ultrasonography, MRCP, and abdominal CT, swollen pancreas was the most common imaging finding in acute and acute recurrent pancreatitis whereas irregular dilatation of the major pancreatic duct in chronic pancreatitis. Conclusion: Abdominal pain was the most common presenting feature of pancreatitis. The common age of pancreatitis was 5-10 years. Idiopathic pancreatitis was found to be most common cause. Imaging studies revealed swollen pancreas in acute and acute recurrent pancreatitis and irregular dilatation of the major pancreatic duct in chronic pancreatitis. BANGLADESH J CHILD HEALTH 2023; VOL 47 (3) : 142-149